Presentation of pediatric Henoch-Schönlein purpura nephritis changes with age and renal histology depends on biopsy timing - Hennies, Imke; Wühl, Elke (Pediatric nephrology, 2018)
Background: This study correlates the clinical presentation of Henoch-Schönlein purpura nephritis (HSPN) with findings on initial renal biopsy.MethodsData from 202 pediatric patients enrolled in the HSPN registry of the German Society of Pediatric Nephrology reported by 26 centers between 2008 and 2014 were analyzed. All biopsy reports were re-evaluated for the presence of cellular crescents or chronic pathological lesions (fibrous crescents, glomerular sclerosis, tubular atrophy >5%, and interstitial fibrosis >5%). Results: Patients with HSPN with cellular glomerular crescents were biopsied earlier after onset of nephritis (median 24 vs 36 days, p = 0.04) than those without, whereas patients with chronic lesions were biopsied later (57 vs 19 days, p < 0.001) and were older (10.3 vs 8.6 years, p = 0.01) than those without. Patients biopsied more than 30 days after the onset of HSPN had significantly more chronic lesions (52 vs 22%, p < 0.001), lower eGFR (88 vs 102 ml/min/1.73m2, p = 0.01), but lower proteinuria (2.3 vs 4.5 g/g, p < 0.0001) than patients biopsied earlier. Children above 10 years of age had lower proteinuria (1.98 vs 4.58 g/g, p < 0.001), lower eGFR (86 vs 101 ml/min/1.73m2, p = 0.002) and were biopsied significantly later after onset of nephritis (44 vs 22 days, p < 0.001) showing more chronic lesions (45 vs 30%, p = 0.03). Proteinuria and renal function at presentation decreased with age. Conclusions: In summary, we find an age-dependent presentation of HSPN with a more insidious onset of non-nephrotic proteinuria, impaired renal function, longer delay to biopsy, and more chronic histopathological lesions in children above the age of 10 years. Thus, HSPN presents more like Immunoglobulin A (IgA) nephritis in older than in younger children.
Published online: 5 October 2017
Gesehen am 04.05.2018